Trace element distribution and mass transfer processes in rutile - Verberne, Rick (Curtin University, 2019)
The trace element geochemistry of rutile (TiO2) is routinely used to constrain the nature and timing of geological events. Its use is underpinned by knowledge of trace element distribution and mobility. In this thesis, atom probe tomography is used to provide a new understanding of the nanoscale processes that affect rutile geochemistry. The results demonstrate the ubiquitous relationship between trace elements and defects that apply to minerals in general and highlight novel applications for geology.